Female Perception of Cohabitation and Marriage in Metropolitan Arequipa - Analucía Torres Flor; Lila Cerellino Cernades; Renzo Rivera (Interacciones)
Background: During the last decades in Peru there have been greater demographic changes, like the remarkable increase in the number of cohabitating couples and the decrease of married ones. Therefore, this study aims to describe the perception of cohabitation and marriage between women in the city of Arequipa, Peru. Methods: 764 women between 18 and 66 years of age were randomly selected according to their socioeconomic level and they were surveyed with a questionnaire about cohabitation and marriage perception. The results indicated that the majority of evaluated women considered marriage important (82.5) because it is the most appropriate way to start living as a couple (35.2%) and it is a legally recognized institution (31.3%), among other reasons. Furthermore, the majority of women do not consider cohabitation as more convenient than getting married (65.8%) and mostly reported that cohabitation is a type of relationship in which members mutually support each other (97.5%), that is exclusive between two people (97%) and in which expenses and duties are shared (95.9%). Conclusion: For a great percentage of cohabiters and single women from the sample, marriage is important. The majority of women do not consider cohabitation more convenient than getting married. The women that considered cohabitation more convenient, pointed two main reasons: knowing if the couple is getting along and knowing the couple well. Less than the 10% of these women believe that cohabitation is a step prior to marriage. Regarding the perception of marriage compared to cohabitation, for the vast majority of women, the perception of cohabitation is similar to the characteristics of marriage.